Isokinetic muscle strength and capacity for muscular knee joint stabilization in elite sailors - Aagaard, P.; Simonsen, E. B.; Beyer, N.; Larsson, B.; Magnusson, P.; Kjaer, M. (International Journal of Sports Medicine, 1997)
In the present study isokinetic dynamometry was used to evaluate the capacity for dynamic knee joint stabilization via muscle contraction in elite sailors (15 males, SM; 6 females, SF) compared to a group of matched controls (8 males, CM). Maximal concentric, eccentric and isometric moment of force (peak moment and moment at 50 degree knee flexion) was obtained for the knee extensors (quadriceps) and flexors (hamstrings) during isokinetic knee joint movement at angular velocities 0, 30, 120 and 180 degrees x s(-1). High levels of eccentric knee extension strength were observed for the elite sailors compared to the controls (p < 0.05). Based on peak moment and 50 degree moment, respectively, conventional hamstring/quadriceps (H/Q) strength ratio (+/-SD) ranged from 0.37+/-0.06 to 0.54+/-0.06 and from 0.42+/-0.07 to 0.57+/-0.10 across groups, speed and contraction mode. The female elite sailors displayed lower (p<0.05) concentric H/Q ratios at 120 and 180 degrees x s(-1) compared to the controls (0.41-0.45 vs. 0.51-0.56, respectively). The ratio of eccentric hamstring to concentric quadriceps strength (H/Q for extension) or concentric hamstring to eccentric quadriceps strength (H/Q for flexion) may provide a more functional estimate of the capacity for muscular knee joint stabilization (1). Based on peak moment and 50 degree moment, respectively, this "functional" H/Q ratio ranged from 0.24+/-0.03 and 0.25+/-0.02 for knee flexion at 180 degrees x s(-1) to 0.97+/-0.17 and 0.88+/-0.12 for knee extension at 180 degrees x s(-1) among the three groups. Comparable levels of "functional" H/Q ratio were observed (p>0.05) for fast knee extension in the elite sailors (SF:0.81-0.97, SM: 0.88-0.95) and the male controls (CM: 0.80-0.84). In conclusion, a "functional" H/Q ratio of 0.8-1.0 observed for all subjects indicated a significant functional capacity of the hamstring muscles for providing muscular stability at the knee joint in fast knee extension. A significant potential for muscular knee joint stabilization appeared for the elite sailors despite their high maximal quadriceps strength and partially lower (SF) conventional H/Q ratios.